The Influence of Work Balance and Organizational Culture on Employee Job Satisfaction at PT Honda Sanggar Laut Palopo - Umra; Muhammad Kasran; Samsinar (LP2M IAIN Palopo, 2025)
In an increasingly competitive era of globalization, companies need to increase competitiveness that cannot be separated from employee contributions, the balance between personal life and work is the most important aspect in increasing job satisfaction. This study aims to examine the effect of work balance and organizational culture on employee job satisfaction at PT Honda Sanggar Laut Palopo. This study uses a quantitative method that focuses on data collection and statistical analysis that aims to answer the researcher's questions and test the hypothesis. The population in this study were 60 employees of PT Honda Sanggar Laut Palopo. The sample in this study used a saturated sample with a total of 52 employees of PT Honda Sanggar Laut Palopo. Data collection was carried out using a google form by distributing questionnaires to respondents who were measured, each item was scored on a Likert scale where each score was from (1) to (5). The data analysis technique for this study was tested using Smartpls4. The results showed that work balance had a positive and significant effect on employee job satisfaction at PT Honda Sanggar Laut Palopo, and organizational culture had a positive and significant effect on employee job satisfaction at PT Honda Sanggar Laut Palopo.